The Role of Organization Culture, Leadership and Training Towards Improving Work Performance Country Civil Worker: Case Study in Financial and Development Supervisory Agency - Ramaditya, Muhammad; Prihantoro, Amirul Wahid (International Journal of Business Studies, 2020)
The objective of this study is analyzed the impact of organizational culture, training, and leadership on the work performance of civil workers in financial and development supervisory agency. This research uses an associative approach with simple random sampling technique which is measured by SEM using the Smart PLS 3.0 application. The population of this study was 330 civil workers in Financial and Development Supervisory Agency (BPKP). The results of the study shown that the Organizational Culture Variables did not significantly influence work Performance of the civil worker in Financial and Development Supervisory Agency, but do not pass the reliability test. Training Variables have a positive and significant effect on the work performance of the civil workers. Leadership variables have a positive and significant effect on the work performance of the civil workers in Financial and Development Supervisory Agency.